(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Biometrics is a mean of forensic recognition based on measurements and calculations of human body or biological features. Human body features. Biometric identification systems may make use of iris, retina, fingerprints, face, ear, gait parameters, facial physiognomy, photogrammetric or geometry features, etc. for recognition and hence identification pursuits. The high security areas like airports, nuclear reactors, thermal or hydro-electric power plants, legislative buildings, defense establishments etc., require secured entry of authorized persons. Biometric tools of recognition like automatic face recognition system can play a crucial role in recognizing illegal intruders to such areas. Iris is an excellent trait to be used in biometric system for recognition of an individual due to its individualistic, unique, universal and inimitable features. In this article, the current national and international status of use of iris patterns for forensic recognition, its advantages and limitations, and future prospects have been presented.